Identifikasi Candida Albican Pada Saliva Wanita Penderita Diabetes Melitus - Farizal, Jon; Abdul Rahman Serbasa Dewa, Exchagusesa (Jurnal Teknologi Laboratorium, 2017)
Diabetes mellitus is a predisposing factor for the onset of oral candidiasis. Women with diabetes have extra sugar in the secretion of saliva. Sugar contained in saliva are stacked on the mucosa so provide food for mold growth so that the diabetic patient saliva will be found Candida albicans The aim of this study was to identify Candida albicans in saliva of women with diabetes mellitus in patient wards of Medicine Hospital Dr M.Yunus Bengkulu 2017.This type of research is conducted by using descriptive survey design. Sampling technique using Purposive Sampling, the number of samples identified as many as 27, conducted by macroscopic and microscopic examination. Data in this research using descriptive analysis.Results of univariate analysis obtained, all respondents the majority of respondents 52% positive saliva fungus Candida albicans and almost half of respondents 48% negative saliva fungus Candida albicans. The prevalence values indicate that the majority of the total population of women with DM saliva samples contained fungus the Candida albicans. Whole saliva respondents (100%) in women with diabetes is growing colonies on Media SDA (Saboraud Dextrose Agar) fungus Candida albicans